Estimating the Effects of Conflict on Education in Côte d’Ivoire - Dabalen, Andrew L.; Paul, Saumik (Taylor and Francis, 2015)
This article evaluates the effect of armed conflict on years of schooling in Côte d’Ivoire. We combine differences in conflict intensity across departments and differences across age cohorts to identify an individual’s indirect exposure to conflict. The difference-in-difference outcomes indicate that the average years of education for a school-going-age cohort is 0.94 years fewer compared to an older cohort in conflict-affected regions. We further use a set of victimization indicators to identify the direct effect of conflict. Overall, the findings across different models suggest a drop in average years of education by a range of 0.2 to 0.9 fewer years. The estimated effect is larger for males and individuals between 19 and 22 years of age.